Weight Changes, Nutritional Intake, Food Contaminants, and Supplements in Women of Childbearing Age, including Pregnant Women: Guidelines for Interventions during the Perinatal Period from the French National College of Midwives. (8th December 2022) - Lecorguillé, Marion; Camier, Aurore; Kadawathagedara, Manik
Abstract: Adequate maternal nutrition is crucial for a healthy pregnancy and optimal fetal growth. Many women in France of childbearing age start their pregnancy in an unfavorable nutritional status. Recent studies highlight the value of paying attention to weight issues from the preconceptional period. It is important to call attention to the need for folate supplementation and to promote a varied and balanced diet throughout pregnancy to cover essential nutritional needs.